MAINTENANCE OF FIELD WORKS TERMS IN SIBERIA - B. D. Dokin; O. V. Elkin; E. A. Lapchenko (Сельскохозяйственные машины и технологии)
Methodical approaches were analyzed for justifying of the field work terms. The concept of economically feasible dates of fieldwork was introduced. They could be more long-time compared with optimal, on condition of equality of the expenses connected with harvest losses because of delay of terms of field works carrying out and expenses caused by technical ensuring these terms. Thus, it is necessary to consider that terms of this or that technological operation don’t coincide for all fields. In addition, agricultural enterprises sowed rye, peas, barley, and other grain crops of different ripening periods: long-duration, intermediate and early. Assignment of costs for maintenance of a technological operation is carried out with taking into account the tractor and agricultural machines using by other technological operations. Analytical expression for determination of economically expedient terms of field works carrying out in the conditions of Siberia was achieved.